Scalable thermochromic smart windows with passive radiative cooling regulation - Wang, Shancheng (2022)
Radiative cooling materials spontaneously radiate long-wave infrared (LWIR) to the cold outer space, providing cooling power that is preferred in hot seasons. Radiative cooling has been widely explored for walls and roofs but rarely for windows, which are one of the least energy-efficient parts of buildings. We fabricated scalable smart windows using a solution process giving different emissivity (ε) at high (εLWIR-H of 0.61) and low (εLWIR-L of 0.21) temperatures to regulate radiative cooling automatically while maintaining luminous transparency and near-infrared (NIR) modulation. These passive and independent visible–NIR–LWIR regulated smart windows are capable of dynamic radiative cooling for self-adapting applications across different climate zones.